Public Value in the Program for Improving Settlement Quality through Gebrak Pakumis in Tangerang Regency (Case Study: Sepatan Timur District) - Juita Anggraeni; Yusmedi Yusuf; Fitria Firdiyani (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study aims to describe and illustrate the public values ​​created by the Gebrak Pakumis Settlement Quality Improvement Program in Tangerang Regency, a case study of East Sepatan. The Gebrak Pakumis Program is designed to improve the quality of settlements consisting of RTLH Rehabilitation, Improvement of Sanitation Facilities, Improvement of Clean Water Facilities and Environmental Management of Settlement Areas. This study uses Mark Moore's Public Value theory. In this theory, public value consists of several indicators, namely Legitimacy and Support, Organizational Capacity, and Substantial Value. This study uses a qualitative research method with a descriptive type. The technique for determining informants in this study uses purposive and snowball sampling techniques. Based on the results of the study, the Gebrak Pakumis Settlement Quality Improvement Program in Tangerang Regency is supported by legitimacy in the form of Tangerang Regent Regulation Number 63 of 2019 concerning Guidelines for the Implementation of the Joint People's Movement Program to Overcome Dense Areas, Slums, Poverty, and Socio-Economic Environmental Empowerment in Tangerang Regency, especially Article 11 paragraph (1) letter a which includes RTLH rehabilitation activities, Improvement of Sanitation Facilities, Improvement of Clean Water Facilities and Environmental Management of Residential Areas. In addition, this program also received support from the community. From the aspect of organizational capacity, it has been supported by human resources, financial resources, and organizational resources, although there are still obstacles in the coordination process and the recruitment process for builders who are less selective, as well as the budget is still limited. Meanwhile, from the aspect of substantial value, this program provides real benefits in the form of economic value, socio-cultural value, and educational value for the community receiving the program in East Sepatan District.